Analysis of structural and metabolic changes in surface microorganisms following powdery mildew infection in wheat and assessment of their potential function in biological control. - Zhen Wu; Xiaodong Xue (PLoS ONE)
Powdery mildew is a highly destructive disease that greatly reduces both the yield and quality of wheat. As there is limited research on changes in microorganism community caused by powdery mildew infection in different tissue parts, especially after spike infection, this study aimed to examine surface microorganisms in infected and healthy wheat plants. Samples were collected from the leaves and spikes, and the number of operational taxonomic units (OTUs), diversity index, abundance, and metabolic changes of the surface microbial community were analysed using 16S rRNA amplicon sequencing technology. Through the identification of surface microbial community in different tissues, 24 phyla were identified in the leaves, and 20 phyla were identified in the spikes. The dominant bacterial phyla observed were Proteobacteria and Bacteroidetes. At the genus level, 19 genera were detected in the leaves, and 11 genera were detected in the spikes. Notably, the total number of genera in the leaves exceeded that in the spikes. The dominant genera were Pseudomonas, Sphingomonas, and Pantoea. At the species level, there were 37 types identified in leaves and 35 types in spikes. The dominant bacterial species identified included Pedobacterium panaciterrae, Pseudomonas baetica, Pseudomonas rhizophaerae, and Sphingomonas aerolata. The analysis conducted in this study revealed that the incidence of powdery mildew was greater in plots situated closer to obstacles than in other plots. Notably, when wheat was infected with powdery mildew, the results indicated that surface microorganisms on both leaves and spikes were significantly impacted, with the response of surface microorganisms on the spikes being more pronounced than that on the leaves. Different from the response of microorganisms on the leaf surface, after infection with powdery mildew, the pathway changes of microorganisms on the spike surface are mainly metabolic regulation. These research results provide theoretical support for the prevention and control of powdery mildew in wheat crops.